3
$\begingroup$

I am given the following equation: $ (y+u)u_x + (x+u)u_y =(x+y)u$ , when: $ u(x,2x)=3x$ .

and I want to solve it using the method of characteristics.

The equations are: $ x_t = y+u , y_t=x+u , u_t = xu+yu$ and I know that I can find the solution using ODE methods (calculating the eigenvalues of the corresponding matrix, etc... ), and the solution is given by: $ x= C_1 e^{-t} + C_3 e^{2t} , y=C_2e^{-t} + C_3 e^{2t} , u= -(C_1 +C_2 ) e^{-t} +C_3e^{2t}$ . When I substitute $ x=s , y=2s, u=3s$ , I get: $ C_3 =2s , C_2 = 0 , C_1 =-s $ and everything looks great ...

The problem is that I can't figure out how to write the solution $u$ explicitly, after substituting the values for the constants $C_i $ ... In addition, when I take the initial condition to be $u(x^2 , -x^2 )= x^2 $ , I get that $u=x $ is a solution, but this solution does not solve the equation itself!

Can someone please explain to me what am I doing wrong ? (The transversality condition seems to be ok in each of the conditions above)

Thanks in advance !

$\endgroup$
  • $\begingroup$ If you can answer your own question, please answer it and accept it as an answer. This is a very welcome deed in this community. $\endgroup$ – Shuhao Cao Sep 12 '13 at 18:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.